Shifting gatekeeping: U.S. political debate regarding Chinese foreign direct investment, 2012-17 - McElwee, L (2021)
This thesis analyzes the evolution of U.S. gatekeeping – herein, policy debate and development – regarding a prominent type of inbound Chinese foreign direct investment (FDI) from 2012 to 2017. This six-year period saw massive change in the bilateral investment relationship, characterizing both the volume of Chinese strategic asset-seeking acquisition attempts in the U.S., and American reception to such attempts. However, existing scholarship focuses on why Chinese acquisitions are controversial in advanced economies, rather than how and why they became controversial over time. Across three studies, this thesis addresses this gap. Using process tracing drawing on hundreds of government and business documents and 37 semi-structured elite interviews, it investigates how and why U.S. gatekeeping shifted toward Chinese acquisitions among the foreign policy executive (FPE), defined as the set of congressional and executive branch entities with purview over China and investment issues.